2022
DOI: 10.1002/aenm.202202983
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Horizontally Stacked Zn Crystals on Single Layer 1T‐VSe2 for Dendrite‐Free Zn Metal Anodes

Abstract: Owing to the moderate redox potential and high safety, Zn metal anodes have been garnering great attention. However, the poor reversibility and limited‐service period caused by side reactions and dendrites hinder their applications. Here, a novel anode material consisting of a hexagonal 1T‐Vanadium diselenide (1T‐VSe2) film on graphene is developed as a zincophilic template to epitaxially electrodeposit hexagonal closest packed Zn to replace the conventional metal substrates in Zn batteries. The 1T‐VSe2/Zn ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…[6][7][8][9][10] Masses of endeavors have been attempted to address these issues mainly in terms of anode surface modification, hierarchical structure design, and electrolyte optimization. [11][12][13][14][15][16][17][18][19] Compared with the complicated processibility of surface modification and structure design, electrolyte optimization has been regarded as one of the most easyto-implement and effective protocols to stabilize the Zn anode. Highly concentrated electrolytes have been substantiated to weaken the solvation interaction between Zn 2+ and H 2 O in the electrolyte by breaking the hydrogen bond (H-bond) network in spite of the high cost, which inspires the widespread exploitation of various inorganic and organic additives.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Masses of endeavors have been attempted to address these issues mainly in terms of anode surface modification, hierarchical structure design, and electrolyte optimization. [11][12][13][14][15][16][17][18][19] Compared with the complicated processibility of surface modification and structure design, electrolyte optimization has been regarded as one of the most easyto-implement and effective protocols to stabilize the Zn anode. Highly concentrated electrolytes have been substantiated to weaken the solvation interaction between Zn 2+ and H 2 O in the electrolyte by breaking the hydrogen bond (H-bond) network in spite of the high cost, which inspires the widespread exploitation of various inorganic and organic additives.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Furthermore, metallic zinc anode with superior theoretical capacity of 820 mAh g −1 , low plating/ stripping potential (−0.78 V vs SHE) in aqueous electrolyte and extremely abundant natural reserves has been regarded as one of the most promising anodes for ZIBs. [2][3][4][5][6] However, the inherent nonuniformity of commercial Zn foils results in non-uniform electric field on the Zn anode surface, which causes preferential Zn 2+ deposition at the tip zone due to its high surface energy. [7] Ultimately, random occurrence of uneven zinc deposition causes rampant zinc dendrites, which results in irreversible capacity loss of the Zn anode and degraded battery lifespan, thus critically restricting the commercial application of Zn anode.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted dendrite formation occurs primarily because of slow ion diffusion to the electrode and inhomogeneous charge distributions. [12] It has been shown that operating conditions such as current density, [13] charging/discharging mode, [14] temperature, [15] substrate chemistry, [16] and electrolyte concentration/ additives [17,18] all influence the electrokinetics. For example, smaller exchange current density yields a slower reduction on the current collector surface, which is believed to promote compact (002) stacking, eliminating dendrite growth.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous computational methods have been used recently to explore battery systems, such as Finite Element Analysis for macro-scale physical properties, [25] Density Functional Theory (DFT) for electronic structure, [26] and classical Molecular Dynamics (CMD) simulation for such atomistic phenomena [16] as atom motion, ionic conductivity, and electrolyte composition. [27,28] DFT molecular dynamics is too computationally expensive to simulate the time or length scales necessary for metal electroplating, while CMD cannot simulate the bond-breaking/forming processes that occur during deposition.…”
Section: Introductionmentioning
confidence: 99%